Heat-shrinkage-resistant PE isolating membrane base membrane and preparation method thereof

By adding core-shell microsphere-fiber composites to the PE isolation film, the problems of insufficient tensile strength and poor light resistance of the PE isolation film are solved, and the high toughness, tear resistance, high temperature resistance and ultraviolet light resistance of the isolation film are improved.

CN119823429AActive Publication Date: 2025-04-15SHANDONG HONGTU NEW MATERIAL TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510317509.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-04-15
Estimated Expiration
2045-03-18

AI Technical Summary

Technical Problem

The tensile strength of the existing PE isolation film is insufficient, and it is easy to have problems such as tensile deformation and wrinkle during the peeling process, and has poor light resistance and is prone to aging and yellowing.

Method used

By adding core-shell microsphere-fiber composites as fillers to the PE isolation film, core-shell microspheres are formed using modified titanium carbon spheres and dispersed nanomica powder, combining γ-aminopropyltriethoxysilane and polyurethane fibers to form the composite, and co-extruded through a twin-screw extruder to improve the toughness and tear strength of the isolation film.

Benefits of technology

It significantly improves the tensile strength and toughness of the PE isolation film, enhances its tear and tensile resistance, improves its high temperature and ultraviolet light resistance, and extends the service life of the isolation film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a heat-shrinkage-resistant PE isolating membrane base membrane and a preparation method thereof, and belongs to the technical field of isolating membranes, titanium dioxide is fixed in hollow titanium carbon sphere structures with hollow interiors, then mica is modified, and the surfaces of modified titanium carbon spheres are uniformly coated with dispersed nano mica, so that the heat-shrinkage-resistant PE isolating membrane base membrane is obtained. The core-shell type microspheres are treated by gamma-aminopropyltriethoxysilane, so that the core-shell type microspheres are gradually loaded on the surfaces of the fibers to form a core-shell type microsphere-fiber compound, when external force acts on the PE isolating membrane, the microspheres and the fibers serve as different stress bearing units and can jointly share the external force, stress concentration can be retarded due to the existence of the microspheres, and the stress concentration of the PE isolating membrane is reduced. The fiber can guide stress transmission, and the titanium dioxide is fixed in the cage-shaped structure with the hollow interior, so that the anti-ultraviolet performance can be continuously exerted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of isolation films, and in particular relates to a heat shrinkage resistant PE isolation film base film and a preparation method thereof. Background Art

[0002] Polyethylene (PE), as a fully saturated hydrocarbon skeleton, is one of the most important commercial polymers and is widely used as a key component of pipes, plates, containers, films, cables, coatings, fibers and other necessities. Semi-finished rubber films need to be made in the process of producing treads, sidewalls, composite layers and belt layers for radial tires. In order to avoid deformation and aging of the films, it is often necessary to attach a separator to the surface of the films. The separator has a good oxygen barrier effect and can prevent oxygen-sensitive films from aging. However, the tensile strength of PE films is not good enough and is easily stretched. When the separator is peeled off from the surface of the film, the separator is prone to tensile deformation, wrinkles and other problems, which can easily affect the overall performance of the separator. In addition, the film has poor light resistance in outdoor light environments and is prone to aging and yellowing.

[0003] A Chinese patent with announcement number CN116656029B discloses a PE isolation cling film for radial tires and a preparation method thereof. By combining polyethylene, a compatibilizer, a polypropylene wax modified fiber material, and filler particles, and utilizing the compatibility effect of the compatibilizer, the bonding compatibility between polyethylene and the polypropylene wax modified fiber material and the filler particles is improved, thereby facilitating the bonding of the isolation cling film with the film; combining the advantage of the low viscosity of polypropylene wax, the isolation cling film is facilitated to be torn off the film surface; and combining the higher strength of the fiber material and the filler particles in the polypropylene wax modified fiber material, the tensile strength of the isolation cling film is improved.

[0004] The above scheme involves the addition of multiple fillers, but the compatibility effect of the compatibilizer alone is not enough to achieve a good dispersion effect of the multiple fillers together, so that the toughness of the isolation film becomes low and it is easy to tear during the stretching process. Summary of the invention

[0005] The object of the present invention is to provide a heat shrinkage resistant PE isolation film base film and a preparation method thereof, by adding a core-shell microsphere-fiber composite as a filler in the PE isolation film base film, avoiding the simple addition of multiple fillers affecting their dispersibility, thereby improving the toughness and tear strength of the PE isolation film base film.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a heat shrinkage resistant PE isolation film base film is prepared by the following steps: Step 1: Add modified titanium carbon spheres, dispersed nano-mica powder and 15-20% sodium dodecylbenzene sulfonate solution into the reactor in a dosage ratio of 20-30g: 3-4g: 3-4mL, stir and mix at 50-65°C and 400-500r / min for 30-40min, transfer the mixture to a fluidized bed, and mix by air flow mill for 15-20min at an air flow rate of 3000-3100mL / min and a feed rate of 0.5-0.6g / min to obtain core-shell microsphere powder.

[0007] Step 2: Add core-shell microsphere powder, γ-aminopropyltriethoxysilane, anhydrous ethanol and deionized water into a reactor, stir at 80-85°C and 400-500r / min for 1-2h, then add polyurethane fiber powder, continue to react for 1-2h, filter, wash the filter cake with deionized water 2-3 times, and vacuum dry to obtain a core-shell microsphere-fiber composite.

[0008] Step 3: Add the core-shell microsphere-fiber composite and high-density polyethylene into a twin-screw extruder at a ratio of 30-40g:500-600g, extrude and granulate at 100-110°C and 50-60r / min to obtain a heat-shrinkable PE isolation film base film.

[0009] Furthermore, the usage ratio of core-shell microsphere powder, γ-aminopropyltriethoxysilane, anhydrous ethanol, deionized water and polyurethane fiber powder is 50-60g: 20-30mL: 300-400mL: 800-900mL: 30-35g.

[0010] Furthermore, the modified titanium carbon spheres in step 1 are prepared by the following steps: The hollow titanium carbon sphere powder and a nitric acid solution with a concentration of 1 mol / L are added into a reactor in a dosage ratio of 20-25 g: 100-120 mL, and the mixture is acid-washed for 1-1.2 h at 50-55°C and 400-500 r / min with stirring, and filtered. The filter cake is washed with deionized water until the last washing liquid is neutral, and then vacuum dried at 60-80°C for 1-2 h to obtain modified titanium carbon spheres.

[0011] Furthermore, the polyurethane fiber powder in step 2 is prepared by the following steps: Polyurethane and dimethylformamide are added into a reaction kettle in a dosage ratio of 50-60 g: 200-300 mL, stirred for 30-40 min at 20-25° C. and 400-500 r / min, wet-spinned using pure water as a coagulation bath, cured for 30-40 min, sheared and crushed to obtain polyurethane fiber powder with a length of 1-2 mm.

[0012] Furthermore, the hollow titanium carbon sphere powder is prepared by the following steps: Chitosan, nickel acetate and 1-2% glacial acetic acid solution by mass fraction are added into a reactor, stirred for 30-40 minutes at 20-25°C and 400-500r / min, then γ-polyglutamic acid and deionized water are added, stirring is continued for 1-2 hours, and then tetrabutyl titanate is added, stirred for 2-3 hours at 50-65°C and 400-500r / min, the product is transferred into a muffle furnace, heated to 700-750°C under a nitrogen atmosphere, and kept warm for 2-3 hours, the product is washed 2-3 times with 30-40% hydrochloric acid solution and deionized water by mass fraction, respectively, and dried in vacuo at 60-80°C for 1-2 hours to obtain a hollow titanium carbon sphere powder.

[0013] Furthermore, the dosage ratio of chitosan, nickel acetate, glacial acetic acid solution, γ-polyglutamic acid, deionized water and tetrabutyl titanate is 20-30 g: 0.2-0.4 g: 200-300 mL: 15-20 g: 200-300 mL: 40-50 mL.

[0014] Furthermore, the dispersed nano-mica powder in step 1 is prepared by the following steps: Add modified nano mica powder, stearic acid, xylene and n-butanol into a reaction kettle, stir for 1-2 hours at 20-25°C and 400-500r / min, filter, wash the filter cake with deionized water 2-3 times, and vacuum dry at 60-80°C for 1-2 hours to obtain dispersed nano mica powder.

[0015] Furthermore, the usage ratio of the modified nano-mica powder, stearic acid, xylene and n-butanol is 15-20 g: 3-4 g: 80-90 mL: 100-120 mL.

[0016] Further, the modified nano mica powder is prepared by the following steps: The modified mica powder and 50-60% ethanol solution by mass are added into a reaction kettle, and ultrasonically crushed for 2-3 hours at a power of 400 W using an ultrasonic device, and then allowed to stand for 48-50 hours, filtered, and the filter cake is washed with deionized water for 2-3 times, and freeze-dried for 12-14 hours to obtain the modified nano mica powder.

[0017] Furthermore, the usage ratio of the modified mica powder and the ethanol solution is 20-22 g: 200-300 mL.

[0018] Further, the modified mica powder is prepared by the following steps: Add crude mica powder, citric acid and deionized water into a reaction kettle, stir for 3-4 hours at 80-85°C and 400-500r / min, filter, wash the filter cake with deionized water until the last washing liquid is neutral, and vacuum dry at 60-80°C for 10-12 hours to obtain modified mica powder.

[0019] Furthermore, the usage ratio of the crude mica powder, citric acid and deionized water is 20-30 g: 40-50 g: 800-900 mL.

[0020] Beneficial effects of the present invention: 1. The heat-shrinkable PE isolation film base film prepared by the present invention is prepared by fixing titanium dioxide in a hollow titanium-carbon ball structure with a hollow interior to form a modified titanium-carbon ball; mica is modified by ultrasonic crushing with citric acid to obtain a modified nano-mica powder with interlayer exfoliation, which is then treated with stearic acid to obtain a dispersed nano-mica, and the dispersed nano-mica is uniformly coated on the surface of the modified titanium-carbon ball to obtain a core-shell microsphere powder; after the core-shell microspheres are treated with γ-aminopropyltriethoxysilane, the core-shell microspheres are gradually loaded on the surface of the fiber to form a core-shell microsphere-fiber composite; the core-shell microsphere-fiber composite and high-density polyethylene are co-extruded through a twin-screw extruder to obtain a heat-shrinkable PE isolation film base film, which has excellent tensile strength and toughness, a rough surface with tight fitting, and excellent high temperature resistance and ultraviolet light resistance.

[0021] 2. The modified titanium carbon spheres of the present invention are intertwined and entangled through the van der Waals force and hydrogen bond interaction of chitosan and γ-polyglutamic acid to form an internal hollow cage structure. Titanic acid generated by hydrolysis of tetrabutyl titanate is impregnated under vacuum to fill the hollow cage structure. Hollow titanium carbon spheres are obtained after carbonization. Titanium dioxide can be fixed in the isolation membrane through this structure. The internal hollow cage structure not only provides sufficient filling space for titanic acid, but also ensures the stability of the titanium carbon spheres in the isolation membrane, thereby ensuring the long-term stability of the isolation membrane performance. The fixation of titanium dioxide makes its photocatalytic performance and UV resistance The performance can be continuously exerted, extending the service life of the isolation membrane; the design of the hollow titanium carbon sphere also gives the isolation membrane a certain self-cleaning ability. Under the action of photocatalysis, titanium dioxide can decompose pollutants attached to the surface of the isolation membrane, thereby keeping its surface clean and smooth. This self-cleaning ability not only helps to improve the aesthetics of the isolation membrane, but also reduces performance degradation and aging problems caused by the accumulation of pollutants; chitosan and γ-polyglutamic acid are natural polymer materials, are biodegradable, and can be decomposed by microorganisms in the natural environment without causing pollution to the environment, which is in line with the concepts of green chemistry and sustainable development.

[0022] 3. The core-shell microsphere-fiber composite of the present invention is formed by uniformly coating the surface of the modified titanium carbon sphere with dispersed nano-mica, thereby forming a core-shell microsphere structure, and then the carboxyl group on the surface of the core-shell microsphere is combined with the amino group of γ-aminopropyltriethoxysilane to graft γ-aminopropyltriethoxysilane on the surface of the core-shell microsphere. Under the action of hydrolysis, γ-aminopropyltriethoxysilane generates silanol groups that react with hydroxyl groups on the surface of the polyurethane fiber, so that the core-shell microspheres are gradually loaded on the surface of the fiber to form a core-shell microsphere-fiber composite. When external force acts on the PE isolation membrane, the core-shell microspheres and the fibers act as different stress bearing units. They can share external forces. The presence of microspheres can slow down the concentration of stress, while fibers can guide the transfer of stress, avoiding excessive local stress that causes the membrane material to rupture, which helps to improve the toughness of the PE isolation membrane. When subjected to external forces such as impact or stretching, the interaction between microspheres and fibers can absorb more energy, thereby enhancing the membrane's tear and tensile resistance. The core-shell microsphere-fiber structure also significantly improves the thermal stability of the PE isolation membrane. In a high-temperature environment, the modified titanium carbon spheres, as an effective thermal barrier, can hinder the rapid transfer of heat and slow down the thermal expansion rate of the membrane material, thereby avoiding deformation or thermal cracking of the membrane due to high temperature. At the same time, the thermal conductivity of the fiber is relatively good, and the heat can be quickly conducted along the fiber direction, which complements the thermal insulation effect of the titanium carbon spheres to achieve uniform distribution and effective management of heat. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1: A method for preparing a heat-shrinkable PE isolation film base film, prepared by the following steps: S1: 20g of crude mica powder, 40g of citric acid and 800mL of deionized water were added to a reactor, stirred at 80°C and 400r / min for 3h, filtered, the filter cake was washed with deionized water until the last washing liquid was neutral, and vacuum dried at 60°C for 10h to obtain modified mica powder; 20g of modified mica powder and 200mL of 50% ethanol solution were added to a reactor, ultrasonically crushed at 400W for 2h using an ultrasonic device, then allowed to stand for 48h, filtered, the filter cake was washed with deionized water twice, and freeze-dried for 12h to obtain modified nano mica powder; 15g of modified nano mica powder, 3g of stearic acid, 80mL of xylene and 100mL of n-butanol were added to a reactor, stirred at 20°C and 400r / min for 1h, filtered, the filter cake was washed with deionized water twice, and vacuum dried at 60°C for 1h to obtain dispersed nano mica powder.

[0025] Modified nano-mica powder, with its nano-scale ultra-thin structure, can be more evenly dispersed in the polymer matrix after being modified with stearic acid. This feature significantly improves the overall performance of the composite material, giving it excellent high temperature resistance and chemical stability, allowing it to maintain excellent performance in high temperature environments. When applied to PE isolation film, the modified nano-mica powder not only enables it to perform well in high-temperature application scenarios, but also gives the isolation film high visible light transmittance and excellent UV shielding properties. This effectively avoids the aging problem of the isolation film caused by direct sunlight during long-term outdoor use, significantly extending its service life.

[0026] S2: 20 g chitosan, 0.2 g nickel acetate and 200 mL 1% glacial acetic acid solution were added to the reactor, stirred at 20 °C and 400 r / min for 30 min, and then 15 g γ-polyglutamic acid and 200mL deionized water were added, and stirring continued for 1h. Then 40mL of tetrabutyl titanate was added, and stirred at 50℃ and 400r / min for 2h. The product was transferred to a muffle furnace, heated to 700℃ under a nitrogen atmosphere, and kept warm for 2h. The product was washed twice with a 30% hydrochloric acid solution and deionized water, respectively, and dried in vacuum at 60℃ for 1h to obtain hollow titanium carbon sphere powder; 20g of hollow titanium carbon sphere powder and 100mL of 1mol / L nitric acid solution were added to the reactor, stirred and acid washed at 50℃ and 400r / min for 1h, filtered, and the filter cake was washed with deionized water until the last washing liquid was neutral, and dried in vacuum at 60℃ for 1h to obtain modified titanium carbon spheres.

[0027] Chitosan and γ-polyglutamic acid are intertwined and entangled through van der Waals forces and hydrogen bonding interactions to form a cage structure with a hollow interior. Titanic acid generated by hydrolysis of tetrabutyl titanate is impregnated under vacuum to fill the interior of the hollow cage structure, and hollow titanium-carbon spheres are obtained after carbonization.

[0028] The self-cleaning effect of nano-titanium dioxide is also based on its photocatalytic properties. Under ultraviolet irradiation, the free radicals generated on the surface of titanium dioxide can not only kill bacteria, but also decompose various organic and inorganic substances. When there is dirt attached to the surface of the PE isolation film, the photocatalytic effect of titanium dioxide can decompose it into harmless substances such as carbon dioxide, water and inorganic substances.

[0029] S3: 20 g of modified titanium carbon spheres, 3 g of dispersed nano-mica powder and 3 mL of 15% sodium dodecylbenzene sulfonate solution were added into a reactor, stirred and mixed at 50 °C and 400 r / min for 30 min, and the mixture was transferred to a fluidized bed, and mixed by air flow milling for 15 min at an air flow rate of 3000 mL / min and a feed rate of 0.5 g / min to obtain core-shell microsphere powder.

[0030] The dispersed nano-mica powder is spread by fluidized bed jet mill and fluidized and collided with modified titanium carbon spheres in the jet mill chamber. Due to the wetting effect of trace surfactants, the dispersed nano-mica and modified titanium carbon spheres can collide on the surface of the microspheres to obtain core-shell microspheres with nano-mica as the shell and modified titanium carbon spheres as the core.

[0031] S4: Add 50g of polyurethane and 200mL of dimethylformamide into a reactor, stir for 30min at 20°C and 400r / min, use pure water as a coagulation bath for wet spinning, solidify for 30min, shear and crush to obtain a polyurethane fiber powder with a length of 1-2mm; add 50g of core-shell microsphere powder, 20mL of γ-aminopropyltriethoxysilane, 300mL of anhydrous ethanol and 800mL of deionized water into a reactor, stir for 1h at 80°C and 400r / min, then add 30g of polyurethane fiber powder, continue to react for 1h, filter, wash the filter cake twice with deionized water, and vacuum dry at 60°C for 1h to obtain a core-shell microsphere-fiber composite.

[0032] S5: 30 g of the core-shell microsphere-fiber composite and 500 g of high-density polyethylene were added into a twin-screw extruder, and extruded and granulated at 100° C. and 50 r / min to obtain a heat-shrinkable PE isolation film base film.

[0033] The carboxyl groups on the surface of the core-shell microspheres are combined with the amino groups of γ-aminopropyltriethoxysilane, so that γ-aminopropyltriethoxysilane is grafted on the surface of the core-shell microspheres. Under the action of hydrolysis, γ-aminopropyltriethoxysilane generates silanol groups which react with the hydroxyl groups on the surface of the polyurethane fibers, thereby gradually loading the core-shell microspheres on the surface of the fibers to form a core-shell microsphere-fiber composite.

[0034] When external force acts on the PE isolation membrane, the microspheres and fibers, as different stress-bearing units, can share the external force together. The presence of microspheres can slow down the concentration of stress, while the fibers can guide the transfer of stress, avoiding excessive local stress that may lead to rupture of the membrane material, which helps to improve the toughness of the PE isolation membrane. When subjected to external forces such as impact or stretching, the interaction between the microspheres and fibers can absorb more energy, thereby enhancing the membrane's resistance to tearing and stretching.

[0035] Example 2: A method for preparing a heat-shrinkable PE isolation film base film, prepared by the following steps: S1: 25 g crude mica powder, 45 g citric acid and 850 mL deionized water were added to a reactor, stirred at 83 °C and 450 r / min for 3.4 h, filtered, the filter cake was washed with deionized water until the last washing liquid was neutral, and vacuum dried at 70 °C for 11 h to obtain modified mica powder; 21 g modified mica powder and 250 mL of 55% ethanol solution were added to a reactor, and ultrasonicated at 400 W using an ultrasonic device. The mixture was crushed for 2.3 hours, then allowed to stand for 49 hours, filtered, the filter cake was washed twice with deionized water, and freeze-dried for 13 hours to obtain modified nano mica powder; 18 g of modified nano mica powder, 3.4 g of stearic acid, 85 mL of xylene and 110 mL of n-butanol were added to the reactor, stirred for 1.2 hours at 23°C and 450 r / min, filtered, the filter cake was washed twice with deionized water, and vacuum dried at 70°C for 1.2 hours to obtain dispersed nano mica powder.

[0036] S2: 25 g chitosan, 0.3 g nickel acetate and 250 mL 1.5% glacial acetic acid solution were added to the reactor, stirred at 23 °C and 450 r / min for 35 min, and then 18 g γ-polyglutamic acid and 250mL deionized water were added, and stirring continued for 1.2h. Then 45mL of tetrabutyl titanate was added, and stirring was continued at 58℃ and 450r / min for 2.3h. The product was transferred to a muffle furnace, and heated to 730℃ under a nitrogen atmosphere for 2.3h. The product was washed twice with a 35% hydrochloric acid solution and deionized water, respectively, and dried in vacuum at 70℃ for 1.2h to obtain hollow titanium carbon sphere powder; 23g of hollow titanium carbon sphere powder and 110mL of 1mol / L nitric acid solution were added to the reactor, and acid washed for 1.1h at 53℃ and 450r / min, and filtered. The filter cake was washed with deionized water until the last washing liquid was neutral, and dried in vacuum at 70℃ for 1.2h to obtain modified titanium carbon spheres.

[0037] S3: Add 25g of modified titanium carbon spheres, 3.4g of dispersed nano-mica powder and 3.5mL of 18% sodium dodecylbenzene sulfonate solution into the reactor, stir and mix at 60°C and 450r / min for 35min, transfer the mixed solution to the fluidized bed jet mill, mix finely, and mix for 18min at an air flow rate of 3050mL / min and a feed rate of 0.55g / min to obtain core-shell microsphere powder.

[0038] S4: Add 60g of polyurethane and 300mL of dimethylformamide into a reactor, stir for 40min at 25°C and 500r / min, use pure water as a coagulation bath for wet spinning, solidify for 40min, shear and crush to obtain a polyurethane fiber powder with a length of 1-2mm; add 60g of core-shell microsphere powder, 25mL of γ-aminopropyltriethoxysilane, 350mL of anhydrous ethanol and 900mL of deionized water into a reactor, stir for 1.5h at 82°C and 500r / min, then add 32g of polyurethane fiber powder, continue to react for 1.5h, filter, wash the filter cake with deionized water 3 times, and vacuum dry at 80°C for 2h to obtain a core-shell microsphere-fiber composite.

[0039] S5: 40 g of the core-shell microsphere-fiber composite and 600 g of high-density polyethylene were added into a twin-screw extruder, and extruded and granulated at 105° C. and 60 r / min to obtain a heat-shrinkable PE isolation film base film.

[0040] Example 3: A method for preparing a heat-shrinkable PE isolation film base film, prepared by the following steps: S1: 30g crude mica powder, 50g citric acid and 900mL deionized water were added to a reactor, stirred at 85°C and 500r / min for 4h, filtered, the filter cake was washed with deionized water until the last washing liquid was neutral, and vacuum dried at 80°C for 12h to obtain modified mica powder; 22g modified mica powder and 300mL 60% ethanol solution were added to a reactor, ultrasonically crushed at 400W for 3h using an ultrasonic device, then allowed to stand for 50h, filtered, the filter cake was washed with deionized water 3 times, and freeze-dried for 14h to obtain modified nano mica powder; 20g modified nano mica powder, 4g stearic acid, 90mL xylene and 120mL n-butanol were added to a reactor, stirred at 25°C and 500r / min for 2h, filtered, the filter cake was washed with deionized water 3 times, and vacuum dried at 80°C for 2h to obtain dispersed nano mica powder.

[0041] S2: 30 g chitosan, 0.4 g nickel acetate and 300 mL 2% glacial acetic acid solution were added to the reactor, stirred at 25 °C and 500 r / min for 40 min, and then 20 g γ-polyglutamic acid and 300mL deionized water were added, and stirring was continued for 2h. Then 50mL of tetrabutyl titanate was added, and stirring was continued at 65℃ and 500r / min for 3h. The product was transferred to a muffle furnace, and heated to 750℃ under a nitrogen atmosphere for 3h. The product was washed three times with a 40% hydrochloric acid solution and deionized water, respectively, and vacuum dried at 80℃ for 2h to obtain hollow titanium carbon sphere powder; 25g of hollow titanium carbon sphere powder and 120mL of 1mol / L nitric acid solution were added to the reactor, and acid washed for 1.2h at 55℃ and 500r / min with stirring, and filtered. The filter cake was washed with deionized water until the last washing liquid was neutral, and vacuum dried at 80℃ for 2h to obtain modified titanium carbon spheres.

[0042] S3: 30 g of modified titanium carbon spheres, 4 g of dispersed nano-mica powder and 4 mL of 20% sodium dodecylbenzene sulfonate solution were added into a reactor, stirred and mixed at 65 °C and 500 r / min for 40 min, and the mixture was transferred to a fluidized bed, and mixed by air flow milling for 20 min at an air flow rate of 3100 mL / min and a feed rate of 0.6 g / min to obtain core-shell microsphere powder.

[0043] S4: Add 60g of polyurethane and 300mL of dimethylformamide into a reactor, stir for 40min at 25°C and 500r / min, use pure water as a coagulation bath for wet spinning, solidify for 40min, shear and crush to obtain a polyurethane fiber powder with a length of 1-2mm; add 60g of core-shell microsphere powder, 30mL of γ-aminopropyltriethoxysilane, 400mL of anhydrous ethanol and 900mL of deionized water into a reactor, stir for 2h at 85°C and 500r / min, then add 35g of polyurethane fiber powder, continue to react for 2h, filter, wash the filter cake with deionized water 3 times, and vacuum dry at 80°C for 2h to obtain a core-shell microsphere-fiber composite.

[0044] S5: 40 g of the core-shell microsphere-fiber composite and 600 g of high-density polyethylene were added into a twin-screw extruder, and extruded and granulated at 110° C. and 60 r / min to obtain a heat-shrinkable PE isolation film base film.

[0045] Comparative Example 1: Based on Example 3, the dispersed nano-mica powder in step S3 is replaced by the coarse mica powder in step S1, and the other steps remain unchanged to prepare a heat shrinkage-resistant PE isolation film base film.

[0046] Comparative Example 2: Based on Example 3, tetrabutyl titanate in step S2 is discarded, and the other steps remain unchanged to prepare a heat shrinkage-resistant PE isolation film base film.

[0047] Comparative Example 3: Based on Example 3, 30 g of crude mica powder, 35 g of polyurethane fiber powder and 30 g of modified titanium carbon balls were stirred and mixed evenly, and the other steps remained unchanged to prepare a heat shrinkage-resistant PE isolation film base film.

[0048] The model of the fluidized bed is AB03.

[0049] Citric acid, chitosan, γ-polyglutamic acid, methyl methacrylate, benzoyl peroxide, and dimethylformamide were purchased from Sigma-Aldrich.

[0050] The performance tests were performed on the heat shrinkage resistant PE isolation film base films prepared in Examples 1 to 3 and Comparative Examples 1 to 3. The results are shown in Table 1: 1. Tensile strength test: Refer to GB / T13022-1991 Plastic Film Tensile Test to test the tensile strength and record the data. The tensile strength is the tensile strength. Glue the isolation film base film to the film surface, let it stand for 2 hours, then tear it off, and then glue it to the film surface again, let it stand for 2 hours, tear it off, repeat the operation 20 times, and record the tensile strength data again, which is the tensile strength.

[0051] 2. Wrinkle detection: After the heat-resistant PE isolation film base film is attached to the film surface, it is rolled up, and then 6 rolled films are stacked to form a 3, 2, 1 structure from bottom to top, 6 in a group. After the 6 rolled films are stacked and placed for 1 day, the isolation film base film on the film surface is torn off, and the wrinkle area of ​​the isolation film base film on the film surface located in the middle of the 3 films in the bottom row is observed, and the wrinkle area per unit area is recorded.

[0052] 3. Testing the bonding effect: After the isolation film base film is bonded to the film surface, observe whether there are hollowing problems on the film surface to evaluate the bonding effect and record the number of hollowing problems on 1 square meter of film; if there are no hollowing problems, it means that the bonding effect is good.

[0053] 4. Use a thermal deformation Vicat softening point tester to test the high temperature resistance of the material, with a heating rate of 100°C / h.

[0054] 5. The tear strength of the release film was measured by the pendulum method according to ASTM D1922-08.

[0055] 6. After each group of test samples has been subjected to UV aging treatment for 72 hours, continue with the performance test.

[0056] Table 1 Performance test table of heat shrink resistant PE isolation film base film

[0057] It can be seen from Table 1 that the tensile strength and heat deformation temperature of the heat-resistant PE isolation film base film prepared in Examples 1 to 3 are significantly better than those of the comparative example. After aging treatment, the degree of decrease in strength and heat resistance temperature is also less than that of the comparative example. The wrinkle area and the number of hollows are significantly lower than those of the comparative example. After aging treatment, the increasing trend of the wrinkle area and the number of hollows is significantly lower than that of the comparative example, indicating that the heat-resistant PE isolation film base film prepared by the present invention has excellent tensile strength and flexibility, a rough surface and close fitting, and excellent high temperature resistance and ultraviolet light resistance.

[0058] In Comparative Example 1, the dispersed nano mica powder is replaced with coarse mica powder. The modified nano mica powder has an ultra-thin structure at the nanoscale. After being modified with stearic acid, it can be more evenly dispersed in the polymer matrix, thereby improving the overall performance of the composite material. After being replaced with coarse mica powder, electrostatic force and van der Waals force exist between the mica particles, which makes it easy for the mica particles to form agglomerates when they are close to each other, thereby affecting the overall performance of the composite material.

[0059] In Comparative Example 2, tetrabutyl titanate is omitted, and titanium dioxide is fixed by the internal hollow cage structure. The cage structure not only provides sufficient filling space for titanium dioxide, but also ensures the stability of the titanium carbon spheres in the isolation membrane.

[0060] In Comparative Example 3, the crude mica powder, polyurethane fiber powder and modified titanium carbon spheres were stirred and mixed evenly. Stirring and mixing alone could not form stable chemical bonds or strong interfacial interactions, resulting in interface defects between the crude mica powder, polyurethane fiber powder and titanium carbon spheres, thereby reducing the mechanical properties of the composite material. By forming a core-shell microsphere-fiber composite, the interface damping can be effectively increased and the external force can be shared.

[0061] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0062] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a heat-shrinkable PE isolation film base film, characterized in that: Prepared by the following steps: Step 1: The hollow titanium carbon sphere powder is acid-washed to obtain modified titanium carbon spheres, and the modified nano mica powder is treated with stearic acid and ultrasonic crushing to obtain dispersed nano mica powder; the modified titanium carbon spheres, dispersed nano mica powder and 15-20wt% sodium dodecylbenzene sulfonate solution are added to the reactor in a dosage ratio of 20-30g: 3-4g: 3-4mL, and stirred for 30-40min. The mixture is transferred to a fluidized bed and mixed by air jet milling for 15-20min to obtain core-shell microsphere powder; Step 2: Add core-shell microsphere powder, γ-aminopropyltriethoxysilane, anhydrous ethanol and deionized water into a reaction kettle, stir for 1-2 hours, then add polyurethane fiber powder, continue to react for 1-2 hours, filter, wash, and vacuum dry to obtain a core-shell microsphere-fiber composite; Step 3: adding the core-shell microsphere-fiber composite and high-density polyethylene into a twin-screw extruder at a mass ratio of 30-40:500-600, extruding and granulating to obtain a heat-shrinkable PE isolation film base film.

2. The method for preparing a heat-shrinkable PE isolation film base film according to claim 1, characterized in that: The usage ratio of the core-shell microsphere powder, γ-aminopropyltriethoxysilane, anhydrous ethanol, deionized water and polyurethane fiber powder in step 2 is 50-60g: 20-30mL: 300-400mL: 800-900mL: 30-35g.

3. The method for preparing a heat-shrinkable PE isolation film base film according to claim 1, characterized in that: The modified titanium carbon spheres described in step 1 are prepared by the following steps: The hollow titanium carbon sphere powder and 1 mol / L nitric acid solution are added into a reactor in a dosage ratio of 20-25 g: 100-120 mL, and pickled for 1-1.2 h at 50-55°C and 400-500 r / min with stirring. The filter cake is washed with deionized water until the last washing liquid is neutral, and vacuum dried to obtain modified titanium carbon spheres.

4. The method for preparing a heat-shrinkable PE isolation film base film according to claim 1, characterized in that: The polyurethane fiber powder in step 2 is prepared by the following steps: Add polyurethane and dimethylformamide into the reactor in the ratio of 50-60g:200-300mL, stir at 20-25℃ and 400-500r / min for 30-40min, use pure water as coagulation bath for wet spinning, solidify for 30-40min, shear and crush to obtain polyurethane fiber powder with a length of 1-2mm.

5. The method for preparing a heat-shrinkable PE isolation film base film according to claim 3, characterized in that: The hollow titanium carbon sphere powder is prepared by the following steps: Chitosan, nickel acetate and 1-2wt% glacial acetic acid solution are added into a reactor, stirred at 20-25°C and 400-500r / min for 30-40min, then γ-polyglutamic acid and deionized water are added, stirring is continued for 1-2h, and then tetrabutyl titanate is added, stirred at 50-65°C and 400-500r / min for 2-3h, the product is transferred into a muffle furnace, heated to 700-750°C under a nitrogen atmosphere, and kept warm for 2-3h, the product is washed 2-3 times with 30-40wt% hydrochloric acid solution and deionized water respectively, and vacuum dried to obtain hollow titanium carbon sphere powder.

6. The method for preparing a heat-shrinkable PE isolation film base film according to claim 5, characterized in that: The dosage ratio of the chitosan, nickel acetate, glacial acetic acid solution, gamma-polyglutamic acid, deionized water and tetrabutyl titanate is 20-30 g: 0.2-0.4 g: 200-300 mL: 15-20 g: 200-300 mL: 40-50 mL.

7. The method for preparing a heat shrinkage resistant PE isolation film base film according to claim 1, characterized in that: The dispersed nano-mica powder described in step 1 is prepared by the following steps: Add modified nano mica powder, stearic acid, xylene and n-butanol into a reaction kettle, stir at 20-25°C and 400-500 r / min for 1-2 hours, filter, wash the filter cake with deionized water 2-3 times, and vacuum dry to obtain dispersed nano mica powder; The usage ratio of the modified nano-mica powder, stearic acid, xylene and n-butanol is 15-20 g: 3-4 g: 80-90 mL: 100-120 mL.

8. The method for preparing a heat shrinkage resistant PE isolation film base film according to claim 7, characterized in that: The modified nano mica powder is prepared by the following steps: Adding modified mica powder and 50-60wt% ethanol solution into a reaction kettle, using an ultrasonic device to perform ultrasonic crushing for 2-3 hours at a power of 400W, then standing for 48-50 hours, filtering, washing the filter cake with deionized water for 2-3 times, and freeze-drying for 12-14 hours to obtain modified nano mica powder; The usage ratio of the modified mica powder and the ethanol solution is 20-22 g: 200-300 mL.

9. The method for preparing a heat-shrinkable PE isolation film base film according to claim 8, characterized in that: The modified mica powder is prepared by the following steps: Add crude mica powder, citric acid and deionized water into a reaction kettle, stir at 80-85°C and 400-500r / min for 3-4h, filter, wash the filter cake with deionized water until the last washing liquid is neutral, and vacuum dry to obtain modified mica powder; The usage ratio of the crude mica powder, citric acid and deionized water is 20-30 g: 40-50 g: 800-900 mL.

10. A heat shrinkage resistant PE isolation film base film, characterized in that: Prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • PE isolation cling film for radial tire and preparation method thereof

    CN116656029B

  • Heat-insulating waterproof composite material and preparation process thereof

    CN116178870A

  • PE isolation preservative film for radial tire and preparation method of PE isolation preservative film

    CN116656029A

  • Preparation method of flexible aerogel composite material

    CN117777525A

  • Anti-aging nanocellulose-based reinforced modified material and preparation method thereof

    CN119490698A